2021
DOI: 10.3390/su132011226
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Biochar–Compost Mix on Growth, Performance and Physiological Responses of Potted Alpinia zerumbet

Abstract: Container crop production has become increasingly popular over the last 50 years. A major component of container or potting media is peat. Peatlands are a natural carbon sink, and peat is a nonrenewable natural resource. Peat harvesting has become an important environmental issue. There is a growing effort to explore alternative organic materials to completely or partially replace peat as a medium component. Biochar is a carbon-rich product that has gained increasing interest as a component of growing media. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…In tomatoes, Massa et al (2019) reported decreased chlorophyll SPAD values under normal and nutritional stress conditions using BC. Similarly, Zulfiqar et al (2021b) reported decreased chlorophyll content in A. zerumbet in response to BC supplementation in a soilless growing medium. SPAD values were also higher in tea plants in response to BC application than in untreated plants (Yan et al, 2021).…”
Section: Influencing Biosynthesis Of Photosynthetic Pigmentsmentioning
confidence: 82%
See 4 more Smart Citations
“…In tomatoes, Massa et al (2019) reported decreased chlorophyll SPAD values under normal and nutritional stress conditions using BC. Similarly, Zulfiqar et al (2021b) reported decreased chlorophyll content in A. zerumbet in response to BC supplementation in a soilless growing medium. SPAD values were also higher in tea plants in response to BC application than in untreated plants (Yan et al, 2021).…”
Section: Influencing Biosynthesis Of Photosynthetic Pigmentsmentioning
confidence: 82%
“…Levesque et al (2020) reported improved growth of tomato and sweet pepper in peat-based growing media incorporating 10% or 15% (v/v) BC, with improved plant water use efficiencies, N and P uptake efficiencies, and increased fruit dry weights. In potted Alpinia zerumbet, Zulfiqar et al (2021b) evaluated the impact of BC incorporation in a peat-perlite-based growing medium; growth improved with 30% BC (v/v) alone or in combination with 5% compost by regulating NPK uptake and leaf gas exchange traits. In Rhododendron delavayi Franch., Bu et al (2022) evaluated the impact of two BC (v/v) applications in peatbased growing media, reporting improved plant and root growth, photosynthesis, and contents of carotenoids, polyphenols, and anthocyanins.…”
Section: Biochar As a Component Of Container Substratesmentioning
confidence: 99%
See 3 more Smart Citations